TRENDS AND IMPLICATIONS OF PROBLEMATIC ASSETS IN CENTRAL COOPERATIVE BANKING SECTOR - Rajendran, P.; Kumar, K.Prabakarraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Irregular assets have emerged as a major concern for the financial stability of Central Cooperative Banks, affecting their profitability and overall efficiency. These assets, commonly referred to as non-performing assets (NPAs), pose significant challenges in terms of recovery and credit expansion. This study explores the nature and causes of irregular assets, their impact on the financial health of cooperative banks, and the strategies adopted for their management. By analyzing existing trends and regulatory frameworks, the study aims to suggest effective measures for minimizing irregular assets and enhancing the performance of Central Cooperative Banks.